Genetic mapping of a single nuclear locus determines the white flesh color in watermelon (Citrullus lanatus L.) - Yi, Licong; Zhou, Wei; Zhang, Yi; Chen, Zibiao; Wu, Na; Wang, Yunqiang; Dai, Zhaoyi (Frontiers in Plant Science, 2023)
Flesh color is an important trait in watermelon (Citrullus lanatus L.). Several flesh color genes have been identified in watermelon; however, the inheritance and molecular basis underlying white flesh trait remains largely unknown in watermelon. In this study, segregation populations were constructed by crossing a canary yellow flesh line HSH-F with a white flesh line Sanbai to fine map the white flesh gene in watermelon. Genetic analysis indicated that the white flesh trait is controlled by a single recessive locus, termed Clwf2. Map-based cloning delimited the Clwf2 locus to a 132.3 Kb region on chromosome 6. The candidate region contains 13 putative genes, and four of them, Cla97C06G121860, Cla97C06G121880, Cla97C06G121890, and Cla97C06G121900 were significantly downregulated in white flesh fruits as compared to canary yellow flesh watermelon fruits. The gene Cla97C06G121890, encodes a tetratricopeptide repeat protein, showed almost no expression in white flesh fruit before maturity, whereas had a very high expression in canary yellow flesh fruit since 18 days after pollination. Transmission electron microscopy revealed rounded and regularly shaped chromoplasts in both canary yellow and white flesh. Further quantitative real-time PCR analysis showed that the expression levels of several key plastid division genes and almost the entire carotenoid biosynthesis pathway genes were downregulated in the white flesh fruits as compared to canary yellow flesh fruits. The findings advance and extend the understanding of the molecular mechanisms underlying white flesh trait formation and carotenoid biosynthesis in watermelon.